Implications of Asset Structuring and Access on Land Tenure in Realizing Agrarian Reform - Robert Dicky Syahputra (Green Publisher Indonesia, 2025)
Agrarian reform is a strategic effort to reorganize the control, ownership, and utilization of land for the creation of agrarian justice in Indonesia. This study aims to analyze government policies in asset management and access to land rights and their legal implications in realizing agrarian reform. The research method uses a normative juridical approach with qualitative analysis of laws and regulations, legal concepts, and case studies. The results of the study showed that asset management was carried out through TORA redistribution and legalization through the PTSL program, while access management was carried out through training, capital provision, infrastructure development, and partnerships. Coordinated implementation through the Agrarian Reform Task Force (GTRA) strengthens cross-sectoral synergy. The legal basis for implementation includes Article 33 paragraph (3) of the 1945 Constitution, the 1960 Law, Presidential Regulation No. 86 of 2018, and the Minister of ATR/BPN Regulation No. 12 of 2021. The legal implications include strengthening legal certainty, protection of agrarian rights, conflict resolution, and transformation of agrarian governance towards a more inclusive and socially just system.